Fabrication of Soft-Oxometalates Mo132 Clusters With Novel Azobenzene Surfactants: Size Control by Micelles and Light - Wang, Zhe; Li, Xuefeng; Chen, Shengli; Dong, Jinfeng (Frontiers in Chemistry, 2021)
Soft-oxometalates (SOMs) are colloid suspensions of superstructured assemblies of polyoxometalates (POMs) and are found to be very effective photo-catalysts in a number of chemical reactions. The stabilization of SOMs generally requires legends or stabilizers eg polymers and surfactants. In this paper, a light responsive azobenzene surfactant, C10AZOC2N3, was developed and used to stable Mo132 SOMs. Various techniques such as DLS, TEM, UV-Vis spectra and cyclic voltammetry were employed to characterize the experimental results. The outstanding structure-directing effect of surfactant self-assembly micelles in solution on inorganic counter-anions was demonstrated. Different amount of cyclohexane was solubilized into C10AZOC2N3 micelles to successfully control the size of Mo132 SOMs cluster. Furthermore, the clusters exposed to UV light for a certain time can be served as a second trigger to control the size of SOMs due to the trans-cis conformation transition of surfactant molecules. The redox potentials of C10AZOC2N3-Mo132 SOMs were investigated as the cluster size varies. Interestingly, the redox potential of Mo132 was not affected by the cluster size, indicating that the presence of surfactant does not change the main function of Mo132 as an electrochemical catalyst, but merely assists in the size control of SOM aggregation.